Implementation of Gamification and Elements of Augmented Reality During the Binary Lessons in a Secondary School - Бузько, Вікторія; Бонк, Алла; Тронь, Віталій (Pedagogy of Higher and Secondary Education, 2018)
Buzko V, L., Bonk A.V. and Tron V.V. Implementation of Gamification and Elements of Augmented Reality During the Binary Lessons in a Secondary School. The purpose of the research is to consider the possibilities of gamification and elements of augmented reality in the secondary school during the binary lessons in Physics and English. The objective of the research is to give examples of conducting binary lessons by means of gaming and elements of augmented reality. The object of the research is the process of teaching Physics and English in a secondary school. The subject of the research is the use of gamification and the elements of augmented reality when conducting binary lessons in a secondary school. The article considers the possibility of introducing the elements of augmented reality and gamification in a secondary school during the binary lessons. Examples of binary lessons for the secondary school students using gamification and augmented reality elements are given. The introduction of various types of educational activities during the binary lessons is analyzed. The results of the research indicate that gamification and the introduction of the elements of augmented reality in the process of studying in a secondary school contribute to the formation and development of cognitive interest of students in Physics and English; it will promote the application of scientific and technical knowledge in real life.